Aproveitamento energético de biogás gerado em reatores UASB tratando esgoto doméstico - Livia Cristina da Silva Lobato (2011)
The research aimed at evaluating the main alternatives for energy recovery from biogas produced in upflow anaerobic sludge blanket (UASB) reactors treating domestic wastewater. The primary focus was related to cogeneration of power and heat for thermal drying and disinfection of the excess sludge. A comprehensive mathematical model was developed in order to estimate that more precisely the fraction of chemical oxygen demand (COD) recovered as methane in the biogas and which, effectively, represented the potential for energy recovery in upflow UASB reactors treating domestic wastewater. The model sought to include all routes of conversion and losses in the reactor, including the portion of COD used for the reduction of sulfates and the loss of methane in the residual gas and dissolved in the effluent. Results from the production of biogas in small- and large-scale UASB reactors were used to validate the model. The results showed that the model allowed a more realistic estimate of biogas production and of its energy potential. Comparison of the main alternatives for energy recovery from biogas produced in UASB reactors treating domestic wastewater indicated that direct combustion with thermal energy recovery is the simplest one and with a better cost/benefit ratio. Cogeneration of power and heat seems to be feasible for nearly all large-scale plants, especially in the case of internal combustion engines. A small unit of cogeneration of energy and heat was tested at the Centre for Research and Training on Sanitation UFMG/COPASA CePTS, located at the Arrudas Sewage Treatment Plant, in Belo Horizonte, Minas Gerais, Brazil. The unit consisted of an engine power generator adapted to run on biogas, a thermal dryer prototype and other peripherals (compressor, biogas storage tank, air blower etc.). The heat from engine power generator exhaust gases was directed towards the thermal dryer prototype to dry the sludge and disinfect it. The results showed that the experimental apparatus is self-sufficient in electricity, even producing a surplus, available for other uses. The tests of drying and disinfection of sludge lasted 7 h, leading to an increase in solids content from 4 to 8% (50% reduction in sludge volume). Although the drying of sludge was not possible (only thickening was achieved), the disinfection process proved very effective, enabling the complete inactivation of helminth eggs.